2021
DOI: 10.1177/2054358120985379
|View full text |Cite
|
Sign up to set email alerts
|

Providing Care for Transgender Persons With Kidney Disease: A Narrative Review

Abstract: Purpose of review: Nephrologists are increasingly providing care to transgender individuals with chronic kidney disease (CKD). However, they may lack familiarity with this patient population that faces unique challenges. The purpose of this review is to discuss the care of transgender persons and what nephrologists should be aware of when providing care to their transgender patients. Sources of information: Original research articles were identified from MEDLINE and Google Scholar using the search terms “trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 213 publications
1
20
0
Order By: Relevance
“…There is no literature suggesting the ranges that should be used when faced with such a dilemma, such as this case, apart from one recent article that discusses the approach to estimated glomerular filtration rate in the transgender population [9]. It has been suggested that both male and female sexes should be considered in eGFR equations for transgender persons on gender-affirming hormone therapy that would provide a range of eGFR by sex that can be narrowed by deciding on which value likely reflects the muscle mass of the patient to which the calculations were applied.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is no literature suggesting the ranges that should be used when faced with such a dilemma, such as this case, apart from one recent article that discusses the approach to estimated glomerular filtration rate in the transgender population [9]. It has been suggested that both male and female sexes should be considered in eGFR equations for transgender persons on gender-affirming hormone therapy that would provide a range of eGFR by sex that can be narrowed by deciding on which value likely reflects the muscle mass of the patient to which the calculations were applied.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that both male and female sexes should be considered in eGFR equations for transgender persons on gender-affirming hormone therapy that would provide a range of eGFR by sex that can be narrowed by deciding on which value likely reflects the muscle mass of the patient to which the calculations were applied. That value of muscle mass can then be used for dosing medications [9].…”
Section: Discussionmentioning
confidence: 99%
“…Collister et al reviewed some of the literature surrounding serum creatinine changes after gender affirmation care and found that creatinine increases approximately 5 to 10 µmol/L in transgender men and decreases 5 to 10 µmol/L in transgender women. 3 In contrast, a recent review found that serum laboratory values were more similar to identified gender than birth-assigned gender in three-fourths studies. 4 The review recommended that creatinine clearance should be calculated with the patient’s identified gender if hormonal therapy had been taken for at least 6 months.…”
mentioning
confidence: 93%
“… 1 , 2 As Collister et al mention in a recent review, “Providing Care for Transgender Persons With Kidney Disease: A Narrative Review,” an accurate estimated glomerular filtration rate (eGFR) is essential in the assessment and treatment of CKD and its associated comorbidities. 3 From our experience, the assessment of renal function should begin with a thorough understanding of the patient’s physical anatomy, medical/surgical history, medication history, and serum lab value history. Collister et al reviewed some of the literature surrounding serum creatinine changes after gender affirmation care and found that creatinine increases approximately 5 to 10 µmol/L in transgender men and decreases 5 to 10 µmol/L in transgender women.…”
mentioning
confidence: 99%
“…In vivo and population-based cohort data describe conflicting effects of sex hormones on kidney function. 6 Although it is unclear whether hormone therapy influences kidney function directly, it typically causes marked physiologic and body composition changes within months after initiation among transgender adults. 7 Increased or decreased percent lean muscle mass, and corresponding increases or decreases in serum creatinine concentrations, may alter creatinine-based kidney function estimating equations.…”
Section: Introductionmentioning
confidence: 99%